2002
DOI: 10.1093/brain/awf045
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visual cortex excitability in blind subjects as demonstrated by transcranial magnetic stimulation

Abstract: Any attempt to restore visual functions in blind subjects with pregeniculate lesions provokes the question of the extent to which deafferented visual cortex is still able to generate conscious visual experience. As a simple approach to assessing activation of the visual cortex, subjects can be asked to report conscious subjective light sensations (phosphenes) elicited by focal transcranial magnetic stimulation (TMS) over the occiput. We hypothesized that such induction of phosphenes can be used as an indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 36 publications
4
53
1
Order By: Relevance
“…In contrast, 9 of 10 SC subjects described phosphenes after occipital TMS (mean intensity threshold, 69 Ϯ 12% of maximal stimulator intensity). Attribution of phosphene locations varied with stimulation sites, in accordance with other studies (20,21).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, 9 of 10 SC subjects described phosphenes after occipital TMS (mean intensity threshold, 69 Ϯ 12% of maximal stimulator intensity). Attribution of phosphene locations varied with stimulation sites, in accordance with other studies (20,21).…”
Section: Resultssupporting
confidence: 91%
“…Thus, similar TMS levels evoke visual experience of phosphenes when applied over occipital cortex in some congenitally blind people, those who are blind but retain some light or motion sensitivity, and sighted subjects (Gothe et al, 2002). However, TMS to occipital cortex elicits no phosphenes in most early blind subjects who have no previous visual function (Gothe et al, 2002). Nevertheless, another study demonstrated interference with Braille reading when TMS was applied to occipital visual areas in early blind subjects (Cohen et al, 1997(Cohen et al, , 1999, which indicates that occipital cortex contributes some function in these people.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, similar TMS levels evoke visual experience of phosphenes when applied over occipital cortex in some congenitally blind people, those who are blind but retain some light or motion sensitivity, and sighted subjects (Gothe et al, 2002). However, TMS to occipital cortex elicits no phosphenes in most early blind subjects who have no previous visual function (Gothe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphenes were elicited by delivering individual pulses of TMS to the right occipital cortex adjacent to the occipital pole. Phosphene threshold values provide a valuable indication of relative cortical excitability; and have been used both as an outcome measure and as a means of determining the appropriate intensity of TMS in variety of studies of human visual perception [8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%